(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Paraoxonase-1 (PON-1) is an anti-oxidant compound considered as negative acute phase protein in animals (Rossi et al., 2013) and people (Novak et al., 2010). The paraoxon-based method for measurement of PON-1 in equine serum has not yet been validated. The aim of this study is to validate a paraoxon-based method to measure PON-1 and to establish reference intervals (RIs) in healthy horses and foals. 120 horses (40 geldings, 40 stallions, 40 mares; median age: 11 years; 57 Warmbloods, 46 Trotters) and 55 foals (27 females, 28 males; median age: 47 days; 22 Warmbloods, 31 Trotters) considered healthy after physical examination and biochemistry were examined. Horses were grouped by breed: Thoroughbreds, Trotters, Warmbloods, Draft horses and Ponies. Serum PON-1 was measured with an automated spectrophotometer and an enzymatic method validated in other species (Giordano et al., 2013). After the analytical validation (precision, accuracy, interference studies), RIs were determined using the Reference Value Advisor software, according to ASCVP guidelines (Friedrichs et al., 2012). The possible gender-, age- and breed-related differences were statistically investigated. The paraoxon-based method was precise (CVs <4.0%) and accurate (P<0.001 in linearity under dilution and spike-recovery testing) but is affected by interference from mild bilirubinemia, severe lipemia or hemoglobinemia. The RIs recorded in the whole population was 38.1-80.8 U/mL. According to the Harris and Boyd test, separate RIs are recommended only for adult females and for Warmblood and Trotter adults (Figure 1). This study demonstrated that analytical performances of the paraoxon-based method for measurement of PON-1 in horses are acceptable. PON-1 is lower in horses than in other species. If future studies will demonstrate that oxidative stress induces a significant decrease of PON-1, this results will be useful to correctly classify healthy and sick horses; PON-1 could be used, as in human medicine, as a marker of oxidative stress.